Fraud prevention in Malaysian small and medium enterprises (SMEs). Issue 2 (8th May 2018) - N'Guilla Sow, Abdoulaye; Basiruddin, Rohaida; Mohammad, Jihad; Abdul Rasid, Siti Zaleha
Abstract : Purpose: In Malaysia, as in most of the developing countries, small businesses play pivotal roles in the economy. Yet, despite the contribution of small businesses, previous researchers have overlooked the fraud issues that are threating the sustainability of those businesses and instead focus mainly on large and public listed companies. Therefore, the purpose of this study is to identify how small businesses can prevent fraudulent activities. Design/methodology/approach: This study used self-administer questioners and distributed 126 questionnaires to general managers, financial managers and supervisors in Malaysian small and medium enterprises (SMEs). Multiple regression was used to test the theoretical model. Findings: The output of multiple regressions showed that culture of honesty and high integrity, anti-fraud processes and controls and appropriate oversight functions has a positive and significant effective on fraud prevention mechanisms. Practical implications: Overall, this study suggests effective fraud prevention measures to mitigate the fraud risk surrounding Malaysian SMEs and other SMEs in emerging countries. Originality/value: There has been a dearth of empirical studies on the effect of culture of honesty, anti-fraud processes and appropriate oversight functions on effective fraud prevention in non-western context, and this study has fulfilled the need for this research.